Safety, tolerability and efficacy of up-titration of guideline-directed medical therapies for acute heart failure (STRONG-HF): a multinational, open-label, randomised, trial - Mebazaa, Alexandre; Davison, Beth; Chioncel, Ovidiu; Cohen-Solal, Alain; Diaz, Rafael; Filippatos, Gerasimos; Metra, Marco; Ponikowski, Piotr; Sliwa, Karen; Voors, Adriaan A; Edwards, Christopher; Novosadova, Maria; et al. (The Lancet (British edition), 2022)
There is a paucity of evidence for dose and pace of up-titration of guideline-directed medical therapies after admission to hospital for acute heart failure. In this multinational, open-label, randomised, parallel-group trial (STRONG-HF), patients aged 18–85 years admitted to hospital with acute heart failure, not treated with full doses of guideline-directed drug treatment, were recruited from 87 hospitals in 14 countries. Before discharge, eligible patients were randomly assigned (1:1), stratified by left ventricular ejection fraction (≤40% vs >40%) and country, with blocks of size 30 within strata and randomly ordered sub-blocks of 2, 4, and 6, to either usual care or high-intensity care. Usual care followed usual local practice, and high-intensity care involved the up-titration of treatments to 100% of recommended doses within 2 weeks of discharge and four scheduled outpatient visits over the 2 months after discharge that closely monitored clinical status, laboratory values, and N-terminal pro-B-type natriuretic peptide (NT-proBNP) concentrations. The primary endpoint was 180-day readmission to hospital due to heart failure or all-cause death. Efficacy and safety were assessed in the intention-to-treat (ITT) population (ie, all patients validly randomly assigned to treatment). The primary endpoint was assessed in all patients enrolled at hospitals that followed up patients to day 180. Because of a protocol amendment to the primary endpoint, the results of patients enrolled on or before this amendment were down-weighted. This study is registered with ClinicalTrials.gov, NCT03412201, and is now complete. Between May 10, 2018, and Sept 23, 2022, 1641 patients were screened and 1078 were successfully randomly assigned to high-intensity care (n=542) or usual care (n=536; ITT population). Mean age was 63·0 years (SD 13·6), 416 (39%) of 1078 patients were female, 662 (61%) were male, 832 (77%) were White or Caucasian, 230 (21%) were Black, 12 (1%) were other races, one (<1%) was Native American, and one (<1%) was Pacific Islander (two [<1%] had missing data on race). The study was stopped early per the data and safety monitoring board's recommendation because of greater than expected between-group differences. As of data cutoff (Oct 13, 2022), by day 90, a higher proportion of patients in the high-intensity care group had been up-titrated to full doses of prescribed drugs (renin-angiotensin blockers 278 [55%] of 505 vs 11 [2%] of 497; β blockers 249 [49%] vs 20 [4%]; and mineralocorticoid receptor antagonists 423 [84%] vs 231 [46%]). By day 90, blood pressure, pulse, New York Heart Association class, bodyweight, and NT-proBNP concentration had decreased more in the high-intensity care group than in the usual care group. Heart failure readmission or all-cause death up to day 180 occurred in 74 (15·2% down-weighted adjusted Kaplan-Meier estimate) of 506 patients in the high-intensity care group and 109 (23·3%) of 502 patients in the usual care group (adjusted risk difference 8·1% [95% CI 2·9–13·2]; p=0·0021; risk ratio 0·66 [95% CI 0·50–0·86]). More adverse events by 90 days occurred in the high-intensity care group (223 [41%] of 542) than in the usual care group (158 [29%] of 536) but similar incidences of serious adverse events (88 [16%] vs 92 [17%]) and fatal adverse events (25 [5%] vs 32 [6%]) were reported in each group. An intensive treatment strategy of rapid up-titration of guideline-directed medication and close follow-up after an acute heart failure admission was readily accepted by patients because it reduced symptoms, improved quality of life, and reduced the risk of 180-day all-cause death or heart failure readmission compared with usual care. Roche Diagnostics.